Methodological approach for assessing relationships in company networks: an application example at a brazilian auto parts industry - Fusco, Prof. Dr. José Paulo Alves; Dias, Profa. MSc. Rosemeire do Carmo Mota (Revista Gestão da Produção Operações e Sistemas, 2012)
Many researchers emphasize the increasing dynamics of business globalization, virtually as a new order ofdriving rules to be considered and included regarding operations management. In this sense, and trying toattain a set of suitable competitive conditions according to the needs of their business, the very internal processesof management and decision making have been growing in terms of complexity and range of issues tobe considered. To do so, it is important to understand and absorb possible changes in competitive conditionsas they arise. This paper aims to present a conceptual model and a case study to illustrate the assessment ofthe relationships involving actors within an operations network. The understanding of the basis behind theserelationships and the identification of the existing hierarchic profile governing them, represent primaryitems to be considered embedded in a decision making system. The results obtained suggest the possibilityto make use of the proposed model as an auxiliary tool to assess existing relationships within an operationsnetwork.Keywords: Network; supply chain; decision making; concurrent networks.